2015
DOI: 10.1186/s40064-015-1469-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of carbohydrate counting and insulin dose calculations among hospital staff in a regional general paediatrics unit

Abstract: The aim of this study was to assess the carbohydrate and insulin knowledge of the staff at Children’s Ark at the University Hospital, Limerick. Carbohydrate counting and insulin dose calculations based on carbohydrates and blood sugars are integral to intensive insulin management of type 1 diabetes mellitus (T1DM). The PedCarbQuiz, a validated questionnaire, was modified, and applied to the staff on our general paediatrics ward. 48/70 eligible staff responded (rate 68 %). Overall knowledge was good: 75.5 % was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Notably, with the use of the CC method, the knowledge scores increased by 4.641 units on average, as compared with not using CC. Therefore, patients with T1DM who intend to perform CC should have more frequent access to qualified dietitians for information on CC and clarification on important issues 20 28. In addition, the CC knowledge scores decreased by −1.039 units on average for every one-unit increase in HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, with the use of the CC method, the knowledge scores increased by 4.641 units on average, as compared with not using CC. Therefore, patients with T1DM who intend to perform CC should have more frequent access to qualified dietitians for information on CC and clarification on important issues 20 28. In addition, the CC knowledge scores decreased by −1.039 units on average for every one-unit increase in HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of the participants stated that they had no difficulty in adjusting insulin dosage by CHO counting method. Similarly, in the study of O'Gorman et al (23), the majority of the participants stated that they had no difficulty in adjusting insulin dosage by CHO counting method. This can be explained by the fact that it is easier to adjust glycemic control by the CHO counting method, with no difficulty adjusting the insulin dose.…”
Section: Discussionmentioning
confidence: 88%
“…It was observed that most of the participants had access to information about CHO counting method from dietitians and least information from books and newspapers. similar to the some other researchers (18,(22)(23). In this situation, individuals with T1DM who perform CHO counting may want to have access to information from dietitian in order to have detailed information about the CHO counting and to answer their questions about it.…”
Section: Discussionmentioning
confidence: 89%
“…However, other studies have shown that adolescents had poor overall knowledge of carbohydrate counting (12,27). In 2015, O'Gorman (28) showed that medical and paramedical staff had a good knowledge (75.5%) in terms of identification of carbohydrates in a meal, but that when they had to calculate the number of carbohydrates in a meal, only 29% succeeded. However, our primary objective was the variation of CI per day and per meal.…”
Section: Discussionmentioning
confidence: 99%